Método de avaliação de sustentabilidade e resiliência urbanas em escala regional: Bacia Hidrográfica Baixo Pardo/Grande (SP) - Alvares, Maria Eugênia Gonçalez (Universidade Federal de São Carlos, 2025)
Disorganized urban growth has generated negative impacts in cities, such as environmental degradation and lack of infrastructure, directly affecting health, quality of life and sustainable development. These conditions can be assessed using indicators, which facilitate analysis using numerical values. The aim of this study was to propose a method for assessing urban sustainability, vulnerability and resilience in the municipalities of Water Resources Management Unit 12 (UGRHI 12), corresponding to the Baixo Pardo/Grande River Basin, using a scale of 0 to 1. The Environmental Health Indicator (ISA), the Sustainable City Development Index (IDSC) and ABNT NBR ISO 37120:2021 Sustainable cities and communities – Indicators for urban services and quality of life, were applied. In the ISA, the Water Supply and Water Resources indicators showed salubrious to average results. The Sanitary Sewage indicator showed that 58% of the municipalities are healthy and sustainable, while only four municipalities achieved an average level for Solid Waste. Vector control was critical in two municipalities (17%) and all of them were deficient in socio-economic terms. As for the Sustainable Development Goals (SDG), the results were mostly average and high, but there was poor performance in SDGs 9, 15 and 17 in all municipalities. In general, the basin has average health and sustainability, requiring investment and planning to improve indicators and quality of life. With regard to NBR ISO 37120, 13 indicators were identified, the average of which showed that 83% of the municipalities are advancing in sustainability and resilience, although some points require attention, such as daily per capita water consumption, which highlighted the need for conscious use. The main limitation was the difficulty in obtaining data, which prevented a complete analysis. In subsequent searches, 41 of the standard's 128 indicators were found (32%). To consolidate the proposed method, called the Index of Sustainability, Vulnerability and Urban Resilience (ISVRU), 10 indicators from the IDSC were selected, giving a total of 51 indicators, classified under the 17 SDGs. The ISVRU is based on the arithmetic average per SDG and the weighted average of the three dimensions analyzed. There was a great lack of programs aimed at sustainable urban planning, which reinforces the need for the Basin Committee to promote actions and debates to improve urban services, quality of life and environmental preservation.
Method for assessing urban sustainability and resilience on a regional scale:: Baixo Pardo/Grande River Basin (SP)
Keywords: Indicadores.; Desenvolvimento sustentável; Vulnerabilidade; Resiliência urbana; Cidades; Indicators; Sustainable development; Vulnerability; Urban resilience; Cities; ENGENHARIAS; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO; ENGENHARIAS::ENGENHARIA SANITARIA